Osteoarthritis-Related Degeneration Alters the Biomechanical Properties of Human Menisci Before the Articular Cartilage - Seitz, Andreas M.; Osthaus, Felix; Schwer, Jonas; Warnecke, Daniela; Faschingbauer, Martin; Sgroi, Mirco; Ignatius, Anita; Dürselen, Lutz (Frontiers in Bioengineering and Biotechnology, 2021)
An exact understanding of the interplay between the articulating tissues of the knee joint in relation to the osteoarthritis-related degeneration process is of considerable interest. Therefore, the aim of the present study is to characterize the biomechanical properties of mildly and severely degenerated human knee joints, including their menisci and tibial and femoral articular cartilage surfaces. A spatial biomechanical mapping of the articulating knee joint surfaces of 12 mildly and 12 severely degenerated human cadaveric knee joints was assessed using a multiaxial mechanical testing machine. To do so, indentation stress relaxation tests were combined with thickness and water content measurements at the lateral and medial menisci and the articular cartilage of the tibial plateau and femoral condyles to calculate the instantaneous modulus, relaxation modulus, relaxation percentage, maximum applied force during the indentation and the water content. With progressing joint degeneration, we found an increase in the lateral and the medial meniscal instantaneous moduli (p<.02), relaxation moduli (p<.01) and maximum applied forces (p<.01), while for the underlying tibial articular cartilage, the instantaneous modulus (p=.01) and maximum applied force (p<.01) decreased only at the medial compartment. Degeneration had no influence on the relaxation percentage of the soft tissues. While the water content of the menisci did not change with progressing degeneration, the severely degenerated tibial articular cartilage contained more water (p<.04) compared to the mildly degenerated tibial cartilage. The results of this study indicate that degeneration-related (bio-)mechanical changes seem likely to be first detectable in the menisci before the articular knee joint cartilage is affected. Should these findings be further reinforced by structural and imaging analyses, the treatment and diagnostic paradigms of osteoarthritis might be modified, focusing on the early detection of meniscal degeneration and its respective treatment, with the final aim to delay osteoarthritis onset.